Perinatal outcome of multiple pregnancy - Saravanan, Susithra; Loganathan, Malarvizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Multifetal gestation in addition to perinatal mortality and morbidity, attributable to preterm delivery they are more vulnerable to unique complications such as, structural malformations and twin- twin transfusion syndrome so that still birth rates are also appreciably increased. The incidence of multifetal gestation following conventional gonadtropin therapy is 16-40% with 75% being twins, with super ovulation it is 25-30%. The incidence of twins and triplets with embryo transfer 22-24% and 26% respectively. Methods: The clinical material taken from institute of Obstetrics and Gynaecology, Egmore Maternity, Chennai. Material for this study consists of 100 multiple pregnancies from May 2001 to April 2002. During this study period 19,617 patients admitted for delivery. There were 99 seats of twins and 1 Triplets. Results: During the period of 1 year, 150 cases were analyzed. During the period 148 cases 2 cases of tripelets studied, no cases of quadruplets were reported during this period. Conclusions: Multifetal gestation is one of the high-risk pregnancies. Hence women with multifetal gestation should ideally receive antenatal care in special twin clinics to meet their special needs. The multi-disciplinary team should be lead by an obstetrician, should include midwives, USG, Neonatologists, social workers and anesthetists. Women followed in twin clinic had significant improvement in women outcome which includes increased mean birth weight, decreased low birth weight and low ICU admissions.